Utility Weight and Quality of Life in Thai Diabetes Mellitus Patients Measured by EQ-5D and Thai DQOL - วงศ์ผัน, ธนะวัฒน์; บุญธรรมเจริญ, กนิษฐา (Journal of Preventive Medicine Association of Thailand, 2018)
In Thailand, the prevalence rate of diabetes mellitus (DM) was 6.9 per 100. Diabetes Mellitus could produce many complications and increase mortality rate. In order to do a health technology assessment for diabetes mellitus, we need a utility weight (UW) to compute quality-adjusted life year. Therefore, this study aimed to (1) measure UW from Euroqol-5D (EQ-5D), (2) analyze factors associated with UW and (3) analyze relation between UW and Thai-Diabetes Quality of Life (DQOL) in multiple conditions such as no complication, nephropathy, neuropathy, retinopathy, glaucoma, cataract, and amputation. We performed cross sectional study; 558 samples were enrolled from out-patients and in-patients in 5 regional hospitals throughout Thailand since 2009-2010. Data analysis was done with Pearson’s correlation and ANOVA. The largest group of samples was collected from Saraburi province (26.2%), average age was 57 (S.D. 12) years old, 40.5% were male, 50.9% were living in suburban area and 73.8% used universal coverage scheme. The UW ranged from 0.42 (S.D. 0.26) to 0.85 (S.D. 0.19). The lowest UW was found in diabetes mellitus with amputation, while the highest one was found in diabetes mellitus without complication. Quality of life could differ from various complications (p<0.05), fasting blood sugar (p<0.001), occupation (p=0.002) and area of living (p=0.03). Moreover, we found significant relation between UW from EQ-5D and the Thai DQOL score (Pearson r=0.519). The key strength of this finding was delivering function to estimate UW by the Thai-DQOL score. The current investigation was limited by lack of amputation details and course of diseases. Thus, further research might explore more detail in severity of the amputation.